Pesantren-Based Inclusive TPQ: A Model for Empowering Quranic Education for Children with Special Needs - Sahal Mahfudh Abdurrahman; Romadhona Azzahro'; Laily Nadia; Umi Nur Sa'adah; Khoirotun Na'imah; Nova Silmi Az Zahra (LP2M of Institute for Research and Community Services - UIN Walisongo, 2026)
Quranic education for children with special needs (CSN) remains a neglected domain within Islamic educational institutions in Indonesia, including at the level of Quranic Learning Centers (TPQ). This article documents and analyzes community service activities in the form of establishing TPQ Inklusi Al-Mubarok in Sukoharjo Village, Margorejo District, Pati Regency, Central Java—the first inclusive TPQ in Pati Regency. The program was pioneered in October 2022 by a lecturer from the Arabic Language Education Study Program at Institut Pesantren Mathaliul Falah (IPMAFA) Pati, in collaboration with student volunteers, Special Education School (SLB) teachers, and institutional support from BAZNAS and the community. Using Participatory Action Research (PAR) and community empowerment approaches, the program designs Quranic learning models tailored to visually impaired, deaf, and speech-impaired learners. Learning media developed include Braille Mushaf, Braille Iqra’, sign language Quran, audio media, and humanistic individual mentoring. Results show: (1) the establishment of Pati’s first inclusive Quranic learning system with 50 students; (2) the emergence of a multi-stakeholder collaborative model among higher education institutions, SLB, BAZNAS, and the community; (3) enhanced competency of IPMAFA students as inclusive da’wah agents; (4) growing public awareness of the religious education rights of CSN. More importantly, the program produced tangible and continuing impacts for the learners themselves: visually impaired students became able to read the Braille Quran and memorize up to several juz through multi-sensory methods, while deaf and speech-impaired students gained the ability to “recite” the Quran through sign language, alongside a restored sense of belonging within the Muslim community. These impacts are designed to be sustainable through a productive-zakat funding scheme (BAZNAS), structured volunteer regeneration, and institutionalized collaboration with the SLB. The novelty lies in an integrative model combining pesantren tradition, inclusive Islamic education, and community-based disability empowerment—a dimension underexplored in Indonesian Islamic community service literature.